Model Pendidikan Keterampilan Tata Boga Bagi Warga Belajar Nonformal Di LKP Nazefa - Adhelia Femmy Nanisa Ghiffari; Husnawati Husnawati; Wahdatan Nisa; Ridwan Ridwan (Jurnal Kajian Ilmiah, 2026)
This study aims to analyze the culinary skills training model for non-formal learning residents at the Nazefa Course and Training Institute. This study analyzes training models related to the stages of planning, implementation, and evaluation of programs. This study uses a descriptive qualitative method by collecting data through direct observation in the field. The results of the study show that at the planning stage, the institution collaborates with the village to record participants from the housewife group through the Samarinda City Government Probebaya Program. At the implementation stage, the training focuses on hands-on practice and participants are allowed to take home the cooking results to maintain the spirit of learning. At the evaluation stage, the assessment is not only carried out when the course is completed, but continues with business assistance so that graduates are ready to face obstacles in the field. These findings suggest that the success of training depends not only on the transfer of technical skills, but also on the suitability of the curriculum to the economic needs of the field. This model enriches the non-formal education literature by emphasizing the importance of systematic program design so that graduates have ready-to-use competencies. The results of this research can be a reference for non-formal education providers in improving the quality of training programs to have a real impact on society.